2016
DOI: 10.1155/2016/4048235
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose BCG Infection as a Model for Macrophage Activation Maintaining Cell Viability

Abstract: Mycobacterium bovis BCG, the current vaccine against tuberculosis, is ingested by macrophages promoting the development of effector functions including cell death and microbicidal mechanisms. Despite accumulating reports on M. tuberculosis, mechanisms of BCG/macrophage interaction remain relatively undefined. In vivo, few bacilli are sufficient to establish a mycobacterial infection; however, in vitro studies systematically use high mycobacterium doses. In this study, we analyze macrophage/BCG interactions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
2
15
0
1
Order By: Relevance
“…bovis BCG was used as model for M. tuberculosis in several assays that required analysis at biosafety level 2 (Fig 3 and 4). However, we feel M. bovis BCG is an adequate substitute for these studies and the data generated here are comparable to M. tuberculosis for a number of reasons: It is well known that M. bovis BCG maintains a high genetic homology and similar cell wall composition to M. tuberculosis (50, 51), and it has been observed here (Fig 1) and in other studies (52)(53)(54) that within the 24-48 hour infection times used in this study, no differences in the bacterial replication rates, trafficking patterns, or host cell viability rates are observed between M. tuberculosis and M. bovis BCG infected cell lines. These common traits at least in the earliest stages of infection allow M. bovis BCG to extrinsically activate TLR signaling and induce hepcidin secretion and intracellular iron retention much like M. tuberculosis (Fig 2 and 3).…”
Section: Discussionsupporting
confidence: 78%
“…bovis BCG was used as model for M. tuberculosis in several assays that required analysis at biosafety level 2 (Fig 3 and 4). However, we feel M. bovis BCG is an adequate substitute for these studies and the data generated here are comparable to M. tuberculosis for a number of reasons: It is well known that M. bovis BCG maintains a high genetic homology and similar cell wall composition to M. tuberculosis (50, 51), and it has been observed here (Fig 1) and in other studies (52)(53)(54) that within the 24-48 hour infection times used in this study, no differences in the bacterial replication rates, trafficking patterns, or host cell viability rates are observed between M. tuberculosis and M. bovis BCG infected cell lines. These common traits at least in the earliest stages of infection allow M. bovis BCG to extrinsically activate TLR signaling and induce hepcidin secretion and intracellular iron retention much like M. tuberculosis (Fig 2 and 3).…”
Section: Discussionsupporting
confidence: 78%
“…The density of the bands was analyzed using the online ImageJ 1.39c software. Actin was used as loading control as reported ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have focused on macrophage activation and death in response to M. tuberculosis , but much less is known about the BCG-mediated cellular activities in the phagocytic cells. 25 Under the experimental conditions used in our study, significant loss in macrophage viability was observed at all times due to the infection, but no significant loss in macrophage viability was observed due to the recombinant BCG strain used ( Fig. 3 ).…”
mentioning
confidence: 59%